Evaluation of Severe Acute Respiratory Syndrome Coronavirus 2 Nucleocapsid Antigen in the Blood as a Diagnostic Test for Infection and Infectious Viral Shedding. (22nd October 2022) - Mathur, Sujata; Davidson, Michelle C; Anglin, Khamal; Lu, Scott; Goldberg, Sarah A; Garcia-Knight, Miguel; Tassetto, Michel; Zhang, Amethyst; Romero, Mariela; Pineda-Ramirez, Jesus; Diaz-Sanchez, Ruth; Rugart, Paulina; et al.
Abstract: Background: SARS-CoV-2 nucleocapsid antigen can be detected in plasma, but little is known about its performance as a diagnostic test for acute SARS-CoV-2 infection or infectious viral shedding among nonhospitalized individuals. Methods: We used data generated from anterior nasal and blood samples collected in a longitudinal household cohort of SARS-CoV-2 cases and contacts. Participants were classified as true positives if polymerase chain reaction (PCR) positive for SARS-CoV-2 and as true negatives if PCR negative and seronegative. Infectious viral shedding was determined by the cytopathic effect from viral culture. Stratified by 7 days after symptom onset, we constructed receiver operating characteristic (ROC) curves to describe optimized accuracy (Youden index), optimized sensitivity, and specificity. Results: Of 80 participants, 58 (73%) were true positives while 22 (27%) were true negatives. Using the manufacturer's cutoff of 1.25 pg/mL for evaluating infection, sensitivity was higher from 0 to 7 days (77.6% [95% confidence interval CI, 64%–88.2%]) than from 8 to 14 days (43.2% [95% CI, 31.1%–54.5%]) after symptom onset; specificity was unchanged at 100% (95% CI, 88.1%–100%). This test had higher sensitivity (100% [95% CI, 88.4%–100%]) and lower specificity (65% [95% CI, 40.8%–84.6%]) for infectious viral shedding as compared with infection, particularly within the first week of symptom onset. Although the presence of N-antigen correlated with infectious viral shedding ( r = 0.63; P < .01), sensitivity still declined over time. Additional cutoffs from ROC curves were identified to optimize sensitivity and specificity. Conclusions: We found that this SARS-CoV-2 N-antigen test was highly sensitive for detecting early but not late infectious viral shedding, making it a viable screening test for community-dwelling individuals to inform isolation practices. Abstract : Evaluation of the SARS-CoV-2 nucleocapsid antigen blood test from our longitudinally sampled cohort suggests that it is a highly sensitive test for detecting early infectious viral shedding, making it a viable screening test for community-dwelling individuals to inform isolation practices.